Malignant infantile osteopetrosis with rickets presenting with bicytopenia in septic shock: case report - Govindarajan, Varun; Mohammed, Thanzir; Jagadish, Meghana; Kariyappa, Mallesh (International Journal of Contemporary Pediatrics, 2021)
Malignant infantile osteopetrosis is a rare, fatal autosomal recessive disorder due to abnormal osteoclast activity. We report a 1-year-old infant, born to consanguineously married couple, who presented to our ER with acute respiratory distress and bicytopenia. He had tender hepatomegaly, splenomegaly, failure to thrive and features of rickets. He was evaluated previously for possible hydrocephalus secondary to his abnormal shape of head with proptosis, MRI revealed a subarachnoid cyst, but possibility of osteopetrosis was missed. Skeletal radiographs done later detected dense, sclerotic bone with sandwich vertebra, provided a delayed diagnosis of MIOP. Rickets, a paradoxical association, was also seen in our case, with low serum calcium and vitamin D3 levels. He succumbed due to severe bronchopneumonia with septic shock. Early diagnosis and timely hematopoietic stem cell transplant are the only curative approach for MIOP, which is otherwise fatal.